A literature review on factors influencing banks’ participation in Islamic syndicated financing - Manap, Aida Noraini; Hassan, Rusni (International Research Centre of Islamic Economics and Finance (IRCIEF), 2018)
The upsurge demand for Islamic financial products has driven the innovation and expansion of syndicated loan into the Shariah compliant financing market known as Islamic syndicated financing. Islamic syndicated financing refers to the participation of a group of financial institutions in a joint financing operation through one of the Shariah permitted modes of financings such as Murabahah and Ijarah. In recent years, Islamic syndicated financing has become one of the important debt funding sources for corporations in need of large financing to finance high value transactions. Despite rising importance, Islamic syndicated financing market share is still low. In the context of Malaysia, Islamic syndicated financing makes up circa 10% contribution of the total syndicated loan volume over the last decade. The smallish contribution is attributed to several challenges such as non-standardization and complexity of documentation, absence of standard methods of syndication, divergence in Shariah approval among participating financiers and nonexistence of same legal platform globally. Besides, there is only a limited body of research on this important form of financing. Owing to these challenges, this study seeks to explore and gather the factors influencing banks’ participation in Islamic syndicated financing. These factors are guided by two theories which are theory of multi-bank lending and theory of financial services marketing by focusing on four out of the seven Ps of services marketing mix. Given the scarcity of academic research on Islamic syndicated financing, this study is therefore conducted based on review of previous work of literature related to factors influencing banks’ participation in syndicated loan to establish depth and breadth on the issues at hand.